The effect of TBC morphology on the erosion rate of EB PVD TBCs - Wellman, Richard G.; Deakin, M. J.; Nicholls, John R. (Elsevier Science B.V., Amsterdam., 2005)
Since thermal barrier coatings (TBCs) have been used in gas turbines most of the research conducted on them has involved the bond coat and the growth of the thermally grown oxide (TGO) as failure of the bond coat and the TGO were considered to be the primary causes of failure. Erosion of TBCs has been considered as a secondary problem and as such received less attention. Most of the initial work on the erosion of TBCs covered the effects of velocity and impact angle on the erosion rates of both plasma sprayed (PS) and electron beam physical vapour deposited (EB PVD) TBCs and compared the differences between the two deposition systems. Most of the tests were conducted on coatings in the as-received condition. This paper aims at expanding the understanding of the erosion of EB PVD TBCs by examining the effects of TBC morphology, column diameter, column inclination angle and the effects of aging and sintering on the erosion rates of EB PVD TBCs. Monte Carlo modelling and mapping of EB PVD TBCs is also briefly discussed along with the associated mechanisms. It was found that, all else being equal, erosion rate decreases with a decrease in the column diameter, while aging results in an increase in the erosion rate, dependent on the aging temperature and time. A decrease in the inclination angle of the columns with respect to the substrate increases the erosion rate, when the inclination angle is less than 60degrees the erosion rate increases catastrophically. These effects are all discussed and explained in terms of erosion mechanisms and mechanical properties in the paper. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: thermal barrier coatings erosion aging morphology thermal barrier coatings damage